Fall field reports contributed by Richard Jule Hollis, 1984 - Hollis, Richard Juleet al (1984)
Fall field reports 1984 was compiled by Richard Jule Hollis. He sighted 15 bird species with three other observers in Iowa City or parts of Johnson County. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed